Portuguese Diaspora Narratives - Padrão, Maria Helena; Vieira, Célia; Rio Novo, Isabel; Oliveira, Clementina; Padrão, Reinaldo (Mediterranean Journal of Social Sciences, 2012)
This study seeks to understand the consequences of this phenomenon (Diaspora) in the relocation of humanresources from other countries to Portugal and to evaluate this impact. With decolonization and later integration into theEuropean Union, some changes occurred in social and cultural identity. Portugal has become a host country. This studyexamines the narratives of the portuguese settlers of Angola and the fiction narratives about this subject. We created a databasewith information about individual characteristics of the portuguese settlers of Angola (gender, age, education level, qualificationlevel, occupation, and emotions). We opted for the use of qualitative method for agreeing Stiles (1993, in Gill, 2000), who arguesthat the purpose of qualitative methods for the condensation of human experience into words isn’t the reduction in its symbolicnumbers. In analyzing the content of these interviews we opted for the analysis of narrative research method that has beenincreasingly used, namely to study specific periods (Farrell, Rosenberg & Rosenberg, 1993, in Zilber et al, 1998), such asmigrations. This project aims to re-interpret and re-think the effects of portuguese diaspora, during and after colonialism periodby giving voice to those who were categorized as returned people. Moreover, this study also aims to take into account thevisions of portuguese writers, in order to consider their perceptions